Development of technology for obtaining an extract from the flowers of Сelosia cristata (L.) Kuntze by applying the method of mathematical planning of the experiment - Deyneka, Alina; Zhuravel, Iryna (Annals of Mechnikov's Institute, 2022)
Introduction. Сelosia cristata (L.) Kuntze is one of the 60 members of the Amaranthaceae L. family and is characterized by high decorative effect. The chemical composition of this plant is represented by saponins, flavonoids, betalaines, amino acids, tannins, alkaloids. Сelosia cristata (L.) Kuntze combed is widely used in traditional medicine. In East Asia, the roots, leaves, flowers and seeds of this plant are used in the treatment of gastrointestinal diseases, blood, eyes, liver, mouth and skin, hematological and gynecological diseases and is an effective remedy for hemorrhoids, hematuria, leukorrhea, jaundice, gonorrhea, eczema, fever, colds, arthritis, cramps, diarrhea and dysentery. Pharmacological studies conducted by foreign scientists have shown that Сelosia cristata (L.) Kuntze is characterized by anti-inflammatory, immunostimulatory, antinoceptic, antitumor, hepatoprotective, antidiabetic, antioxidant, wound healing, antiviral, antimicrobial, antimicrobial, anti-inflammatory. This indicates the prospects for the development of new drugs based on raw cellophane. It is known that the efficiency of the process of extraction of BAS from medicinal plant raw materials largely depends on the created extraction conditions. However, the selection of optimal conditions under which the maximum yield of BAS is achieved, requires numerous experiments with alternating variation of individual factors, which in turn is a time-consuming, high-cost process and does not assess the impact of all factors on the process. The method of mathematical planning of the experiment allows to reduce the number of scientific researches, to rationalize, optimize and intensify them, at the same time to reduce the error and to obtain the most reliable and scientifically substantiated results at minimum costs. The practical application of this approach allows to speed up and significantly reduce the cost of drug development. The aim of the work was to select the optimal conditions for obtaining of Сelosia cristata (L.) Kuntze flowers of dense extract. Materials and methods. For the experiment, air-dry, crushed Сelosia cristata (L.) Kuntze flowers were used. Raw materials were harvested in 2019-2021 in the Kharkiv region. Results and discussion. According to the results of mathematical planning, the extremum of the response function was within the range of variable factors. The predicted value of the extremum of the response function was 5.56% with values of ethanol concentration factors 78.48%, extraction temperature 66.32 ° C and the ratio of raw material and extractant 0.2 (1: 5). Since it is difficult to comply with the parameters of the extremum point in industrial conditions and requires additional economic costs, therefore, the optimal conditions for obtaining an extract from the flowers of Сelosia cristata (L.) Kuntze were chosen ethanol concentration of 70%, extraction temperature – 60 ° C, raw material ratio – 0.2 (or 1: 5). Under such conditions, the predicted value of flavonoid yield was 5.35 %. In practice, the content of flavonoids in the extracts obtained under given conditions was equal to 5.02 %, which was 93.83 % of the maximum predicted value. To increase the yield of these BAS to 5.19 % allows the use of triple extraction. Conclusions. The method of mathematical planning showed that the optimal conditions for obtaining an extract from the flowers of Сelosia cristata (L.) Kuntze were three times extraction with 70 % ethanol at a ratio of raw material and extractant 0.2 (or 1: 5) and extraction temperature 60 ° C, which provides maximum flavonoid yield – 5.19 %. The obtained results of the experiment will be taken as a basis for the development of drugs based on the flowers of Сelosiacristata (L.) Kuntze. Key words: Сelosia cristata (L.) Kuntze, Amaranthaceae L., extraction, method of mathematical planning. DOI: 10.5281/zenodo.6634779